The Arrogance of Power : The Secret World of Richard Nixon - Summers, Anthony; Swan, Robbyn (London Phoenix Press, 2000)
This 'brilliant and mind-boggling' account of Richard Nixon's career, from his youth in California to the turbulent days of his presidency, presents a stark portrait of a man whose personal torments had such a damaging impact on a whole nation
Include Illustration, Note and Index
Keywords: Presidents -- United States -- Nixon, Richard M. (Richard Milhous), 1913-1994 -- Psychology -- Politics and government